Epidemiologia e análise molecular de Leptospira spp. patogênicas em morcegos do estado Rio Grande do Sul, Brasil - Ulsenheimer, Bruna Carolina (2022)
Leptospirosis is caused by bacteria of the genus Leptospira spp. which has a considerable impact on the economy, public health and animal health, characterized by being a zoonosis with worldwide distribution and high occurrence in Brazil. Leptospira spp. is present in rural and urban environments and it is transmitted by direct or indirect contact, especially with the urine of infected animals. In this way, domestic and wild species can harbor the microorganism in the renal tubules and serve as a source of infection for other hosts, demonstrating the broad infectious spectrum of this disease among mammals. Studies on the presence of Leptospira spp. in wild and synanthropic animals are relevant to demonstrate the distribution of leptospirosis in a given region. Within this context, the chiropterans are an important order of wild animals, which act as a reservoir for the bacterium and can transmit it to other species of animals and even to man, thus bats can act as reservoirs for leptospirosis in different regions. Due to the importance of this disease to public health and the lack of knowledge about the epidemiological profile of leptospirosis in bats, we seek to collaborate with the elucidation of the ecoepidemiology of this important zoonosis in Rio Grande do Sul, Brazil. To this end, we aim to carry out a molecular and phyloepidemiological investigation of Leptospira spp. in bat kidney tissue. Total DNA was extracted from 102 kidney tissue samples from different bat species and cities in Rio Grande do Sul, Brazil. The polymerase chain reaction was used to amplify a fragment corresponding to the LipL32 gene, which exclusively detects Leptospira spp. pathogenic. Of the analyzed samples, the DNA of this bacterium was detected in 22.5% (23/102) of the bat kidney tissue samples. Most of the bat species collected were classified as insectivores: 12.7% (13/102) Tadarida brasiliensis, 2.9% (3/102) Molussus correntium, 2% (2/102) Molossus rufus, and 1% (1/102) Histiotus velatus, Myotis levis and Lasiurus blossevillii. The presence of DNA from Leptospira spp. pathogenic was detected in insectivorous bats, by phylogenetic analysis and it was observed that Leptospira interrogans is circulating in bats in the south of the country, an important region of international transit of people and animals among Brazil, Uruguay and Argentina. Additionally, it is emphasized that this was the first study that used phylogenetics analyses to detect L. interrrogans in bats in Brazil. Molecular detection of Leptospira spp. pathogenic in bats demonstrates the participation of chiropterans in the chain of leptospirosis infection and, therefore, they may play an important role as reservoirs and disseminators of this microorganism. In addition, there is a need to monitor infectious agents, especially those with zoonotic potential in wild animals.